1969
DOI: 10.1113/jphysiol.1969.sp008681
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acidaemia on the response to stimulation of the autonomic nerves to the heart

Abstract: SUMMARY1. The effects are described of an acidaemia produced either by an inhalation of carbon dioxide or by an infusion of hydrochloric acid on the response of the heart to stimulation of the ansae subclaviae and right vagus nerve in anaesthetized dogs.2. The results show that during an acidaemia (pH 6.95) of up to 2 hr duration the response to stimulation of the right vagus nerve was enhanced and that the inotropic response to stimulation of sympathetic nerves was not changed; the chronotropic response was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

1970
1970
1989
1989

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…Although all preparations showed a decline in pH after 2 hr. the degree of acidaemia was always much smaller than that which has been shown to affect efferent nerves to the heart (Linden & Norman, 1969). Cardiovascular reflexe,8.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although all preparations showed a decline in pH after 2 hr. the degree of acidaemia was always much smaller than that which has been shown to affect efferent nerves to the heart (Linden & Norman, 1969). Cardiovascular reflexe,8.…”
Section: Introductionmentioning
confidence: 96%
“…It was suggested by Ledsome & Linden (1964), and shown by Linden & Norman (1969), that cardiovascular reflexes may be affected by acidaemia. As acidaemia is a likely consequence of anaesthesia and positive pressure ventilation with an open chest, arterial pH was measured in thirteen experiments of this series.…”
Section: Introductionmentioning
confidence: 99%
“…Millar & Morris, 1961). Therefore it has been suggested that the occurrence of acidaemia may be a contributing factor preventing the observation of reflex increases in heart rate involving efferent sympathetic nerves (Linden & Norman, 1969). The present investigation examines the effect of acidaemia on the reflex increase in heart rate elicited from stimulation of left atrial receptors.…”
Section: Physiology Department Manchester Universitymentioning
confidence: 90%
“…Walsh, , 1970 (Ledsome & Linden, 1964. Severe acidaemia (< pH 7.0) reduces the chronotropic response to stimulation of sympathetic nerves to the heart (Linden & Norman, 1969). Acidaemia is known to occur in anaesthetized, surgically traumatized animals (e.g.…”
Section: Physiology Department Manchester Universitymentioning
confidence: 99%
“…These animals were being used in investigations of the effects of anaesthesia on acid-base balance (Ledsome, Linden & Norman, 1971), in studying the effects of changes in the arterial carbon dioxide tension on acid-base balance Linden & Norman, 1966), in studies of the effects of acidaemia on the responses of the heart to autonomic nerve stimulation (Linden & Norman, 1969), in a study of reflexes arising from the left atrium and a study of the use of propranolol .…”
Section: Methodsmentioning
confidence: 99%